Correlation Family’s Healthy Lifing Behavior with Diarrhea in Toddlers - Asnel, R; Sari, L A (KnE Life Sciences, 2019)
Diarrhea is a continuous stimulation of defecation and feces that still have excess water content, defecate more than three times a day and usually last more than two days. Diarrhea is the second leading cause of death in toddlers after pneumonia. Diarrhea can be prevented through the application of family’s healthy living behavior (breastfeeding history, use of clean water, hand wash habits of toddlers and use of healthy latrines, weigh toddlers every month). The purpose of study was to determine the correlation between family’s healthy living behavior and diarrhea in toddlers. This research is quantitative analytical survey use cross sectional study. The Sample’s number were 90 mothers who have toddlers at integrated service post in the working area of Rejosari Pekanbaru Public Health Center. Sampling using simple random sampling technique, use questionnaire, then analysed with chi square test. The results of this study concluded that four variables correlation with the incidence of diarrhea, they were exclusive breastfeeding history, use of clean water, hand wash habits of toddlers and use of healthy latrines. One variable which no correlation that weigh toddlers every month. It is expected that the community can apply healthty living behavior in family to prevent toddler from diarrhea. Keywords: Diarrhea, toddlers, family’s healthy living behavior